Analisis Pengaruh Pertumbuhan Ekonomi, Pertumbuhan Penduduk Dan Tingkat Inflasi Terhadap Kemiskinan Di Provinsi Jawa Barat - Gita Cici Septiani; Muchtolifah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Poverty is the inability of a person to fulfill their daily needs. West Java is one of the major provinces in Indonesia. Like other big cities, West Java has a social problem that needs more attention from the government, namely poverty. According to poverty data in 3 provinces on the island of Java, namely West Java, Central Java and East Java in 2020 based on urban and rural areas, poverty in the West Java region in urban areas is the highest when compared to the provinces of Central Java and East Java. This study aims to determine the effect of economic growth, population growth and inflation on poverty in West Java. The data used are secondary data for the 2006 - 2020 time period obtained from BPS West Java. The analytical tool used in this study is multiple linear regression analysis using the SPSS program. The results obtained are population growth has a significant effect on poverty in West Java, but the variables of economic growth and inflation have no significant effect on poverty in West Java.